Impact of the roadkill of a jaguar cub (Panthera onca) on social networks and the inhabitants of Sinaloa, México - Rubio-Rocha, Yamel; Chávez-Tovar, Cuauhtémoc; Gaxiola-Camacho, Soila; Ayala-Rubio, Mariana; Alvarado-Hidalgo, Daniel; Pérez-Camacho, Alexis; Sicairos-López, Jesús (Therya Notes, 2022)
Vehicle traffic on roads is a risk factor for wildlife; the death of wild animals by collision involves direct adverse effects at the population level, especially for endangered species such as the jaguar (Panthera onca). This note reports the first roadkill record of a jaguar cub and its impact on the inhabitants of southern Sinaloa, México. The collision occurred in November 2020 on the road running adjacent to the Meseta de Cacaxtla Ecological Reserve. Information on the jaguar cub roadkill was distributed by the people that rescued the corpse and media awareness. About 50 thousand people were reached or informed through social networks. Environmental education workshops, conferences, and webinars were conducted in several villages across the region to raise awareness and for drivers to take precautions to prevent accidents threatening the well-being of wild fauna and road users.